Changes in landscape composition of differently irrigated hay meadows in an arid mountain region. Issue 2 (21st October 2014) - Riedener, Eliane; Melliger, Ramona L.; Rusterholz, Hans‐Peter; Baur, Bruno; Hölzel, Norbert
Abstract Questions Does the recent change from traditional to sprinkler irrigation result in alterations in the surrounding landscape of species‐rich hay meadows in an arid Swiss mountain region? Are landscape composition and landscape heterogeneity important determinants of plant diversity in these meadows? Location Southwestern Switzerland. Methods We surveyed vascular plant species in six traditionally and six sprinkler‐irrigated hay meadows. Plant species were divided into grassland specialists and generalists. Individual landscape traits were assessed in circular areas with radii of 50 and 100 m around each meadow in a field survey. Aerial photographs were used to measure the percentage area covered by different habitat types in the present and prior to the installation of sprinklers at the same spatial scale as in the field surveys. The potential effects of irrigation technique and present‐day landscape features on the plant diversity and species composition of hay meadows were examined with GLM and NMDS. Results Landscape composition was more diverse for traditionally than for sprinkler‐irrigated meadows, but did not differ prior to the installation of sprinklers. Total plant species richness and the number of specialists were negatively affected by the distance to the closest haystack. Generalists were positively influenced by a variety of different small‐scale landscape traits in the surroundings, whereas the percentage area covered by woodland had a negative effect. Finally, hay meadows irrigated with sprinklers had an increased number of generalist plant species. Conclusions This study showed that the small‐scale surroundings, and to some extent the type of irrigation, are important for the conservation of plant diversity of these meadows. Furthermore, the study suggests that the installation of sprinklers was associated with a homogenization of the landscape, which facilitates land use. Extensive management should be promoted by compensation payments for farmers to prevent intensification.